Foliar or soil applications of silicon alleviate water-deficit stress of potato plants - Pilon, Cristiane [UNESP]; Soratto, Rogério P. [UNESP]; Broetto, Fernando [UNESP]; Fernandes, Adalton M. [UNESP] (Amer Soc Agronomy, 2014)
Root-supplied Si is thought to play a role in alleviating the effects of water-deficit stress in several crops. However, little information is known about the contribution of Si, especially foliar application, in the biochemical and physiological mechanisms of potato (Solanum tuberosum L.) under water-deficit stress. The objective of this study was to evaluate the effects of soil-and foliar-applied soluble Si on Si accumulation, osmotic adjustment, antioxidant defense responses, pigments concentrations, and tuber yield of potato plants grown under water deficit. A greenhouse experiment was conducted using pots containing 35 dm(3) of a Typic Acrortox soil. Treatments included a control (no water-deficit stress or Si application), water-deficit stress (-0.060 MPa soil matric potential) without Si application, water-deficit stress with soil-applied soluble Si (50 mg dm(-3) Si), and water-deficit stress with foliar-applied soluble Si (five sprays of 1.425 mM Si water solution). Soil-applied Si increased concentration and accumulation of Si in all parts of water-stressed potato plants while foliar-applied Si increased the Si concentration only in the tuber + roots, compared to the control and water-deficit treatment. Both soil-and foliar-applied Si increased proline, activity of catalase (CAT), and tuber dry weight and decreased hydrogen peroxide (H2O2) concentration in water-stressed plants. The activity of superoxide dismutase (SOD) was increased only by the foliar application of Si. Water-stressed plants that received either soil-or foliar-applied Si maintained relative water content, concentrations of chlorophyll a and carotenoids, chlorophyll a/b ratio, and tuber yield similar to well-watered potato plants.